Stress test analysis of http using Jmeter and QUIC / Muhammad Abdullah Daniel Zulkarnain - Zulkarnain, Muhammad Abdullah Daniel (2021)
Nowadays, the internet is getting big with information from anywhere around the world that has the potential to change the world as we know. It is hard to detect or manage HTTP/HTTPS that is suitable to perform the specific function or run an easy test like authentication on the internet website. JMeter is a client application that can use to testing or check the website performance by doing the stress test. The application of This tool is developed by Apache that supports java that can run on all operating systems. These tools use creating requests to a target server and simulate several users and the server will respond. Once the JMeter done gathers data to calculate statistical information it will provide a performance report and result that can display errors and other detailed information about the target server.